2012
DOI: 10.1162/jocn_a_00146
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Cognitive–Emotional Interplay in Moral Decision-making

Abstract: This study investigated the temporal dynamics of emotional and cognitive processing underlying decision-making in moral judgment. Thirty-seven participants were presented with a set of 60 dilemmas varying in whether killing one individual was an intended means to save others (instrumental dilemmas) or a foreseen but unintended consequence (incidental dilemmas). Participants were required to decide between Options A (letting a specific number of people die) and B (killing one person to save a specific number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(117 citation statements)
references
References 35 publications
10
103
2
1
Order By: Relevance
“…Moreover, dispositional differences in cognitive empathy predict neural differentiation during moral evaluations, but only after 300ms. Consistent with a growing body of recent literature (e.g., Lahat et al, 2013; Sarlo et al, 2012), these findings support a complex conception of morality involving early differentiation between prosocial and antisocial actions, followed by a secondary reappraisal of these actions. It is this later reappraisal that is heavily impacted by individual dispositions.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, dispositional differences in cognitive empathy predict neural differentiation during moral evaluations, but only after 300ms. Consistent with a growing body of recent literature (e.g., Lahat et al, 2013; Sarlo et al, 2012), these findings support a complex conception of morality involving early differentiation between prosocial and antisocial actions, followed by a secondary reappraisal of these actions. It is this later reappraisal that is heavily impacted by individual dispositions.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the P2 component (a positive wave peaking around 200 ms after stimulus onset) was also found to be related to moral processes. A larger P2 was found in the frontopolar and frontal areas when subjects decided on instrumental rather than incidental dilemmas (Sarlo et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…As a prior study found the P2 to be associated with moral decision-making (Sarlo et al, 2012), we expected that it might be related to moral responses. Finally, given that later components of the ERP, such as the LPP and slow wave, were found to reflect moral evaluations (Chiu Loke, Evans, & Lee, 2011;Yoder & Decety, 2014), we expected that these components would reveal specific moral distinctions under each emotional arousal condition.…”
Section: Introductionmentioning
confidence: 98%
“…In the Footbridge dilemma , the only way to save the five is to push a large stranger off an overpass, so that his body would stop the trolley. It is a well-known and widely replicated result that individuals usually endorse the choice to sacrifice one person to save five lives in the Trolley dilemma, but not in the Footbridge dilemmas (Greene et al, 2001; Schaich Borg et al, 2006; Hauser et al, 2007; Sarlo et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we might expect that a more intense negative emotional state would be related to a lower percentage of utilitarian choices. However, evidence of an association between self-report ratings of the emotional state experienced by participants and moral judgments or choices has been mixed: of the few studies that collected participants’ emotional evaluations during the task (Choe and Min, 2011; Sarlo et al, 2012; Lotto et al, 2014; Szekely and Miu, 2015; Horne and Powell, 2016), only one (Horne and Powell, 2016) reported an association between emotions and moral judgment, and none reported an association between emotional ratings and choices. In a study by Krosch et al (2012) that used realistic military scenarios, participants that reported having based their choices on their emotional reaction were more likely to choose a “humanitarian” option (protecting civilians from being attacked) over a “military” one (not acting in order to preserve neutrality).…”
Section: Introductionmentioning
confidence: 99%